2016
DOI: 10.1371/journal.pone.0149585
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Genetic Profiles of Campylobacter in Commercial Broiler Production from Breeder to Slaughter in Thailand

Abstract: Poultry and poultry products are commonly considered as the major vehicle of Campylobacter infection in humans worldwide. To reduce the number of human cases, the epidemiology of Campylobacter in poultry must be better understood. Therefore, the objective of the present study was to determine the distribution and genetic relatedness of Campylobacter in the Thai chicken production industry. During June to October 2012, entire broiler production processes (i.e., breeder flock, hatchery, broiler farm and slaughte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 46 publications
7
21
1
3
Order By: Relevance
“…Of 70 fecal samples collected from the chickens, 48 tested positive, which was 68.5% of all samples tested. High carriage of this genus of bacteria in birds is confirmed by the latest research conducted by a team from Thailand (Prachantasena et al, ), who reported the occurrence of these bacteria in 75% of birds tested. Results obtained by British researchers showed the presence of Campylobacter spp.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Of 70 fecal samples collected from the chickens, 48 tested positive, which was 68.5% of all samples tested. High carriage of this genus of bacteria in birds is confirmed by the latest research conducted by a team from Thailand (Prachantasena et al, ), who reported the occurrence of these bacteria in 75% of birds tested. Results obtained by British researchers showed the presence of Campylobacter spp.…”
Section: Discussionmentioning
confidence: 59%
“…Campylobacter bacteria are one of the main causes of contamination of poultry carcasses in the slaughterhouse, and these carcasses are the primary source of campylobacteriosis infections in humans (Hwang et al, 2009 Thailand (Prachantasena et al, 2016), who reported the occurrence of these bacteria in 75% of birds tested. Results obtained by British researchers showed the presence of Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…In simple attribution models using MLST data, C. jejuni and C. coli isolates from chickens in the Netherlands, Senegal and the United States have been more closely related to UK chicken isolate populations rather than to populations from other host species in the same country (Sheppard, Colles et al., ). While genomic signatures of host association can transcend geographical structuring within C. jejuni and C. coli populations, there can be differences in the genotypes that are isolated from different countries (Asakura et al., ; Islam et al., ; Kivisto et al., ; Mohan et al., ; Prachantasena et al., ). This presents challenges, not only for attributing the source of infections among travellers returning from foreign locations (Mughini‐Gras et al., ), but also for understanding disease epidemiology in the context of a global food industry.…”
Section: Discussionmentioning
confidence: 99%
“…Thailand, Campylobacter jejuni and Campylobacter coli are found most commonly in production and processing [41][42][43]. Antimicrobial resistance is present in many cases [41].…”
Section: Inmentioning
confidence: 99%